Multi-parameter optical gauge based on mode coupling effect in asymmetric index multi-core fibres. (July 2022) - Arrizabalaga, Oskar; Sun, Qi; Lee, Timothy; Zubia, Joseba; Pascual, Javier Velasco; Ocariz, Idurre SÁez De; SchÜlzgen, Axel; Amezcua-Correa, Rodrigo; Brambilla, Gilberto; Beresna, Martynas
Highlights: Provides advantages that include ultrahigh sensitivity, wide detection range and good stability. The asymmetric mode coupling between cores is introduced allows to fabricate optical gauges with the ability to detect and differentiate different types of deformation in structures using just a single sensor. superior performance of this novel optical gauge over the commercially available sensors and offer the highest sensitivities. An important breakthrough of the asymmetric mode coupling between cores is its ability to simultaneously monitor curvature and its direction. The proposed technology could be key to the fabrication of new fiber-based sensing devices with more capabilities and better features than previously achieved. Abstract: An optical gauge based on coupled multi-core fiber is proposed and experimentally demonstrated. By using direct laser writing to selectively break the fiber index profile symmetry, asymmetric mode coupling between cores is introduced. This allows to fabricate optical gauges with the ability to detect and differentiate different types of deformation in structures using just a single sensor. The fabricated optical gauges are compared with calibrated commercial gauges and fiber Bragg gratings as strain, vibration and curvature gauge. The tests indicate superior performance of this novel optical gauge over the commercially available sensors and offer the highest sensitivities. The proposed technology could be key to the fabrication of new fiber-based sensing devices with more capabilities and better features than previously achieved.